1935
DOI: 10.1021/ja01315a105
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Interatomic Distance on Single Bond-Double Bond Resonance1

Abstract: The data for chrysene [J. Iball, ibid., ¿146, 140 (1934)] are also compatible with this value.(20) The value 1.41 Á. has also been reported for the carboncarbon distance in benzene derivatives. We think it probable that this is 0.02 Á. too large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
1

Year Published

1957
1957
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(103 citation statements)
references
References 0 publications
7
95
0
1
Order By: Relevance
“…However, if this is done, then we obtain a value of 3.98 for N 2 , 0.046 for Li 2 and 0.230 for Cu 2 . The value for N 2 is much too high to represent a triple bond, while those for Li 2 and Cu 2 are much too low to represent a single bond. Clearly, the Pauling formula is not easily extended to other regions of the periodic table.…”
Section: Experimental Bond Ordersmentioning
confidence: 97%
See 3 more Smart Citations
“…However, if this is done, then we obtain a value of 3.98 for N 2 , 0.046 for Li 2 and 0.230 for Cu 2 . The value for N 2 is much too high to represent a triple bond, while those for Li 2 and Cu 2 are much too low to represent a single bond. Clearly, the Pauling formula is not easily extended to other regions of the periodic table.…”
Section: Experimental Bond Ordersmentioning
confidence: 97%
“…We might, then, expect a viable definition of bond order to include contributions from the internuclear distance as well as the force constant. In fact, much of the literature concerning this topic involves examination of either the relationship of bond order to internuclear distance [2] or the relationship between force constant and internuclear distance [34], often with the bond order as mediator. For example the work of Kavanau [35] suggested that the internuclear distance could be written as a function of principal quantum numbers raised to the power of the bond order.…”
Section: Experimental Bond Ordersmentioning
confidence: 99%
See 2 more Smart Citations
“…A 40% contribution of the structure with the double bond between the carbon atom and the nitrogen atom would confer upon this bond the property of planarity of the group of six atoms. The estimate of 40% double-bond character for the C-N bond is supported by the experimental value of the bond length, 1.32 Å, interpreted with the aid of the empirical relation between double-bond character and inter-atomic distance 2 . Knowledge of the structure of amides and also of the amino acids, provided by the theory of resonance and verified by extensive careful experimental studies made by R. B. Corey and his coworkers, has been of much value in the determination of the structure of the amide complexes.…”
Section: Fig1 Resonance Structures Of Amide Groupmentioning
confidence: 67%